OP0151 Docosahexaenoic acid treatment of rheumatoid arthritis: a randomized, double-blind, placebo-controlled, cross-over study. (15th June 2017) - Neumann, T; Dawczynski, C; Dittrich, M; Goetze, K; Welzel, A; Oelzner, P; Voelker, S; Schaible, AM; Troisi, F; Thomas, L; Pace, S; Koeberle, A; et al.
Abstract : Background: Epidemiological studies and clinical investigations indicate a beneficial impact of long-chain n-3 polyunsaturated fatty acids (n-3 PUFA) on the inflammatory activity of rheumatoid arthritis (RA). However, the knowledge about the physiological effects of the individual compounds eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) is limited. Objectives: In our pilot study presented here, we investigated the clinical benefit of daily intake of foods enriched with microalgae oil as source of DHA in RA patients. In particular, the influence on disease activity and changes in the profile of pro-inflammatory/non-resolving and anti-inflammatory/pro-resolving lipid mediators was examined. Methods: This is a randomized, double-blind, cross-over study on 38 patients (32 females/ 6 males) with active RA (DAS28≥2.4). They were allocated to consume foods enriched with microalgae oil from Schizochytrium sp. (2.1 g DHA/day) or sunflower oil (placebo) for 10 weeks while maintaining stable immunosuppressive treatment. Results: Thirty-two patients finished the study but seven patients were excluded from analysis because their DHA increase in erythrocyte lipids (EL) was less than 25% after 10 weeks of intervention indicating insufficient adherence to the intervention. Supplementation of DHA led to a decline in tender joints (TJ68) 8.4±5.6 to 6.0±5.0 (p=0.03), swollen joints (SJ66) 5.6±3.5 to 3.9±3.5 (p=0.07) and DAS28 4.3±1.0 to 3.9±1.2 (p=0.07). Joint counts in the placebo arm remained stable (TJ68) 6.7±4.9 to 8.8±8.0 (p=0.12), swollen joints (SJ66) 3.5±3.0 to 4.2±3.7 (p=0.40) and DAS28 4.0±0.9 to 4.1±1.2 (p=0.45). Ultrasound score (US-7) remained stable (15.1±9.5 to 12.4±7.0; p=0.160) while it increased in the placebo arm (11.4±7.0 to 14.0±8.8; p=0.03). The amount of n-3 PUFA in erythrocyte increased in supplemented patients (7.0±1.2% to 10.6±1.4%; p<0.001) and the ratios of aracidonic acid (AA) /EPA (18.5±6.3 to 12.6±5.5; p<0.001) and AA/DHA (3.8±1.0 to 1.8±0.6; p<0.001) dropped significantly. Fatty acid distribution in erythrocyte lipids (n-3 PUFA, AA/EPA and AA/DHA) remained stable in the control arm. Conclusions: The study shows that microalgae DHA supplements can ameliorate disease activity in patients with active RA along with a shift in the balance of AA- and DHA-derived lipid mediators towards an anti-inflammatory/pro-resolving state. Disclosure of Interest: None declared